THE EFFECTS OF IMPLICIT VERSUS EXPLICIT INSTRUCTIONS TO TEACH REFUSAL STRATEGIES ON STUDENTS’ SOCIOPRAGMATIC AND PRAGMALINGUISTIC COMPETENCE - Trifita Handayani (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Abstract The purposes of the study were to explain the effects of implicit instruction on student’s sociopragmatic competences, implicit instructions on students’ pragmalinguistic competences, explicit instructions on students’ sociopragmatic competences, explicit instructions on students’ pragmalinguistic competences, the differences between implicit and explicit instructions on students’ sociopragmatic competences, the differences between implicit and explicit instructions on student’s pragmalinguistic competences, and the interaction between instructions with the students’ sociopragmatic and pragmalinguistic competences. The study used a quantitative research by using experimental factorial design 2x2. The data were taken from 80 second semester students at English Language Education Study Program at STAIN. The result of the study revealed that the mean score of post-test in implicit instruction on students’ sociopragmatic was 80.000 while explicit 92.550. Meanwhile, the mean score of post-test in implicit instruction on students’ pragmalinguistic was 83.000 while explicit 95.5000. It could be concluded that explicit has better effect to teach refusal strategies than implicit instruction on students’ sociopragmatic and pragmalinguistic competence based on the difference between the means score on implicit and explicit.